Unequal Development and Capitalism: Catching Up and Falling Behind in the Global Economy - Adalmir Antonio Marquetti; Alessandro Miebach; Henrique Morrone (Routledge, 2024)
Unequal development has been a defining characteristic of capitalism. Throughout history, countries and regions have exhibited differences in labor productivity growth – a key determinant in poverty reduction and development – and although some nations may catch up with the productivity levels or well-being of developed economies at times, others fall behind. This book explores these processes of catching up and falling behind of developing countries from Asia, Latin America, Central and Eastern Europe, and Africa in relation to the US economy from 1970 to 2019. The research presented in this book integrates a historical interpretation of post-World War II capitalism with economic theory and empirical analysis. By exploring the historical experiences of these countries, the book provides an overview of their economic transformations. The interplay between technical change, profit rate and capital accumulation, on one hand, and institutional change, on the other, are combined to explain the dynamics of catching up or falling behind in labor and capital productivities. Furthermore, the book provides, from the perspective of developing countries, fundamental lessons for the implementation of successful strategies for catching up and development. This book is a major resource for readers interested in economic growth and development, heterodox macroeconomics, development economics, and related areas.
Keywords: 330; unequal; development; capitalism; global; economy